REMOVED: Analisis Kepuasan Konsumen di Jatiroso Catering Service - Mukhamad Arianto; Nur Mahmudah (JBMP (Jurnal Bisnis, Manajemen dan Perbankan), 2014)
This article was removed at the request of the authors due to developments in the reported case. Removed article: https://doi.org/10.21070/jbmp.v1i2.267 Removal notice: https://doi.org/10.21070/jbmp.v5i1.2066